2017
DOI: 10.1097/sla.0000000000002368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Hospital Readmission Reduction Program on Surgical Readmissions Among Medicare Beneficiaries

Abstract: Objective To understand the impact of the Hospital Readmission Reduction Program on both future targeted and non-targeted surgical procedures. Summary Background Data The Hospital Readmission Reduction Program, established under the Affordable Care Act in March of 2010, placed financial penalties on hospitals with higher-than-expected rates of readmission beginning in 2012 for targeted medical conditions. Multiple studies have suggested a “spill-over” effect into other conditions, but the extent of that effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 20 publications
2
56
0
5
Order By: Relevance
“…[7][8][9][10][11] Unplanned readmissions have been shown to be associated with poor clinical outcomes and increased health care costs (estimated at $17.4 billion per year for all unplanned readmissions within the Medicare system in 2004). [12][13][14] The Patient Protection and Affordable Care Act and the associated Hospital Readmissions Reduction Program were implemented in 2010 to assess performance on the basis of readmission after certain index conditions and charge penalties to hospitals with higher-than-expected readmission rates. 15,16 Surgical oncology patients, particularly those undergoing therapies with a high risk of postoperative complications, present a particularly vulnerable population for readmission.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Unplanned readmissions have been shown to be associated with poor clinical outcomes and increased health care costs (estimated at $17.4 billion per year for all unplanned readmissions within the Medicare system in 2004). [12][13][14] The Patient Protection and Affordable Care Act and the associated Hospital Readmissions Reduction Program were implemented in 2010 to assess performance on the basis of readmission after certain index conditions and charge penalties to hospitals with higher-than-expected readmission rates. 15,16 Surgical oncology patients, particularly those undergoing therapies with a high risk of postoperative complications, present a particularly vulnerable population for readmission.…”
Section: Introductionmentioning
confidence: 99%
“…or knee replacement [30][31][32]. Model 2 of the Medicare Bundled Payments for Care Improvement initiative, which started in 2013 and encouraged hospitals to voluntarily participate in bundled payments for 1 or more of 48 episodes of care, was also shown to be associated with reduced rates of institutional PAC use and reduced duration of PAC after hip or knee replacement 2.…”
mentioning
confidence: 99%
“…After the 2012 implementation of the Hospital Readmissions Reduction Program by the Centers for Medicare and Medicaid Services (CMS), 15,16 many hospitals developed internal strategies to reduce their readmission rates, [17][18][19][20] and several national campaigns were launched to help hospitals decrease readmission rates globally. 21 Although these efforts were largely directed at Medicare beneficiaries and for specific target conditions, studies have revealed that such hospital-wide efforts successfully decreased readmission rates in nonpenalized conditions, [22][23][24] and multiple pediatric-specific initiatives have been launched simultaneously. [25][26][27] Nevertheless, almost nothing is known about national trends in pediatric readmission rates during this time.…”
mentioning
confidence: 99%